2009
DOI: 10.3171/2008.5.17560
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ventriculoperitoneal shunt dependency in patients with aneurysmal subarachnoid hemorrhage

Abstract: An FRI score created by discriminant function analysis can predict whether or not a permanent shunt is required, even if separate factors are not in agreement with each other or show a weak correlation when considered separately. An increased FRI score was strongly and linearly correlated with the risk of EVD challenge failure. A prospective study is necessary to validate the FRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
64
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 37 publications
6
64
0
1
Order By: Relevance
“…Gruber et al 7 reported that ruptured aneurysms located in the anterior communicating artery conferred a significant increased risk for the development of sNPH compared with those in other locations (p < 0.001). Other previous studies concluded that patients with a ruptured posterior circulation aneurysm most frequently developed sNPH; 1,5,6,12,16,17,21 3 of these 7 studies reported that patients with an anterior communicating artery or ACA aneurysm are the second-most frequent to develop sNPH and that developing sNPH after an MCA aneurysm is rare. 6,17,21 The other 4 studies did not further categorize the anterior circulation aneurysms as being located in the ACA, MCA, or ICA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gruber et al 7 reported that ruptured aneurysms located in the anterior communicating artery conferred a significant increased risk for the development of sNPH compared with those in other locations (p < 0.001). Other previous studies concluded that patients with a ruptured posterior circulation aneurysm most frequently developed sNPH; 1,5,6,12,16,17,21 3 of these 7 studies reported that patients with an anterior communicating artery or ACA aneurysm are the second-most frequent to develop sNPH and that developing sNPH after an MCA aneurysm is rare. 6,17,21 The other 4 studies did not further categorize the anterior circulation aneurysms as being located in the ACA, MCA, or ICA.…”
Section: Discussionmentioning
confidence: 99%
“…6,17,21 The other 4 studies did not further categorize the anterior circulation aneurysms as being located in the ACA, MCA, or ICA. 1,5,12,16 The sNPH risk conferred by posterior circulation aneurysms may be affected by the other modified variables, such as intraventricular hemorrhage and acute hydrocephalus, for which the frequency was reported to be the highest in patients with a ruptured posterior circulation aneurysm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Large thirdventricle diameter (approximately 7 mm), high CSF protein levels, higher Hunt and Hess grade, and the presence of intraventricular blood have all been shown to be predictors of shunt dependency in patients with SAH who have developed hydrocephalus. 5,24 Post-SAH hydrocephalus is unique because of the variability in intracranial pressure (ICP). It is important not to assume that an elevated ICP is always present in such patients.…”
Section: Discussionmentioning
confidence: 99%